(untitled) (Terr@ Plural, 2022)
The Cerrado biome occupies approximately 22% of the Brazilian territory. The state of Paraná has records of this vegetation in seven municipalities, including Campo Mourão, which reached 102 km² in area. Currently, the remnants of Cerrado in the municipality are concentrated in the urban area, mainly in the Prof.ª Diva Aparecida Camargo Cerrado Ecological Station - EEC (smallest Cerrado do Brasil ecological station with 13,330 m2) and lot 7H ( 22,000 m²). This work brings the first sketch about the perception of residents around the EEC. For this, 25 residents were interviewed (semi-structured questions). As a result, the organizational map of the social representation of the Station was obtained, having as its central core the elements “Good/Good” and peripheral elements e.g. “important, trees, taste, preservation, fresh and abandoned”. The result indicated a predominantly positive evaluation the residents. However, there is little understanding of the importance of the Cerrado and the EEC.